Simulasi Penggunaan Intrusion Detection System (IDS) Sebagai Keamanan Jaringan dan Komputer - Barany Fachri; Fadli Hamdi Harahap (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
In the current era of information technology, computer network security is part of a system that is very important to maintain the validity and integrity of data and to ensure the availability of users' morning services from anywhere and anytime. And on one hand humans are very dependent on information systems. That causes the statistics of network security incidents to increase sharply from year to year. So we need a solution to overcome this, one of which is by simulation. Simulations are carried out to simulate existing real network security systems with properties that are easier to observe than the original system, to determine system performance. In this research, a system that is able to cope with threats that may occur optimally in a fast time is needed, this will speed up the process of handling disruptions and system or service recovery. One way that can be used to overcome or overcome this is to use the Intrusion Detection System (IDS). One application that supports intrusion detection system (IDS) is Snort. Snort is able to do an analysis of the forms of intruder attacks that misuse network protocols